Genome-Wide Identification, Characterization, and Expression Analysis of the Grapevine Superoxide Dismutase (SOD) Family - Xiaoxuan Hu; Chenyu Hao; Zong-Ming Cheng; Yan Zhong (International Journal of Genomics)
Superoxide dismutase (SOD) is an essential enzyme of the plant antioxidant system that responds to oxidative damage caused by adverse conditions. However, little is known about the SOD gene family in Vitis vinifera (Vv). In the present study, ten SOD genes, including 6 copper/zinc SODs, 2 iron SODs, and 2 manganese SODs, were identified in the grapevine genome where they were unevenly distributed on 12 chromosomes. Ten VvSOD genes were divided into three main groups based on phylogenetic analysis, subcellular localization, and the distribution of conserved protein motifs. Additionally, many cis-elements related to different stresses were found in the promoters of the 10 VvSOD genes. Syntenic analysis revealed that VvMSD1 and VvMSD2 were derived from segmental duplication, and VvCSD4 and VvCSD5 belong to a pair of tandemly duplicated genes. Gene expression analysis based on microarray data showed that the 10 VvSOD genes were expressed in all the tested tissues. Interestingly, the segmentally duplicated gene pair (VvMSD1 and VvMSD2) exhibited differential expression patterns in various organs. In contrast, the tandemly duplicated gene pair (VvCSD4 and VvCSD5) displayed similar expression patterns in the tested organs. Our results provide a basis for further functional research on the SOD gene family in grapevine.